Clinical dynamic visual acuity in patients with cerebellar ataxia and vestibulopathy - Dankova, Michaela; Jerabek, Jaroslav; Jester, Dylan J; Zumrova, Alena; Paulasova Schwabova, Jaroslava; Cerny, Rudolf; Kmetonyova, Silvia; Vyhnalek, Martin (PloS one, 2021)
Deterioration of dynamic visual acuity (DVA) as a result of impaired vestibulo-ocular reflex (VOR) has been well described in peripheral vestibulopathies, however, changes in DVA in patients with degenerative cerebellar ataxias (CA) and its relation to VOR impairment in these patients has not yet been evaluated. Our aim was to assess the alterations of DVA in CA and to evaluate its relation to vestibular function. 32 patients with CA and 3 control groups: 13 patients with unilateral and 13 with bilateral vestibulopathy and 21 age matched healthy volunteers were examined by clinical DVA test, VOR was assessed by video Head Impulse Test and caloric irrigation. The severity of ataxia in CA was assessed by Scale for the assessment and rating of ataxia (SARA). Relationship between DVA and vestibular function in CA patients was examined by linear regressions. DVA impairment was highly prevalent in CA patients (84%) and its severity did not differ between CA and bilateral vestibulopathy patients. The severity of DVA impairment in CA was linked mainly to VOR impairment and only marginally to the degree of ataxia. However, DVA impairment was present also in CA patients without significant vestibular lesion showing that central mechanisms such as impairment of central adaptation of VOR are involved. We suggest that the evaluation of DVA should be a standard part of clinical evaluation in patients with progressive CA, as this information can help to target vestibular and oculomotor rehabilitation.
Keywords: senioři; Reflex, Vestibulo-Ocular; Head Impulse Test; bilaterální vestibulopatie; Vestibular Function Tests; cerebelární ataxie; Middle Aged; mužské pohlaví; Cerebellar Ataxia; studie případů a kontrol; pulsní rotační test; Adult; ženské pohlaví; Humans; zraková ostrost; Visual Acuity; lidé středního věku; vestibulární nemoci; vestibulookulární reflex; Bilateral Vestibulopathy; vestibulární funkční testy; Case-Control Studies; dospělí; Vestibular Diseases; Female; Aged; lidé; Male